The Effect of Yoga Exercise on Menstrual Pain Reduction - Asmalinda, Wita; Lukita, Leoni Ripayu; Sapada, Edy (Poltekkes Kemenkes Jakarta III, 2022)
Pain mechanism is an integrated process of sensory input, emotional and cognitive systems. The body responds to pain as a feeling of discomfort. Menstrual pain is caused by increased uterine contractions and angiospasm triggered by prostaglandins F2 and E2. This study aims to determine how yoga exercises reduce menstrual pain in high school students. This type of research is quasi-experimental with a comparison group (pre and post-test with control group design). The study was conducted at SMA Negeri 6 Palembang for 30 days, from October 10 to November 10, 2021. The study sample was all class XI students who met the inclusion and exclusion criteria of 50 respondents. The homogeneity of the respondents' characteristics was assessed using the Kolmogorov-Smirnov test. Description analysis to determine the mean and standard deviation. The bivariate test used was Paired t-test with a significance degree of 0.05. From the results, it was found that the average score of menstrual pain was significantly decreased in the treatment group compared to the control group, with a p-value of 0.002. This study concludes that yoga exercise affects reducing menstrual pain.